IS IT USEFUL A1C FOR DIAGNOSIS AND FOLLOW-UP OF DIABETES MELLITUS TYPE 2? - Ángela Luongo; Silvana Milrad; Alicia Beatriz García; Eva López González; María Ruiz Morosino; María Varela; Bárbara Arinovich; Claudio Daniel González (Revista de la Sociedad Argentina de Diabetes, 2020)
Aims: Analize the value given by physicians to the hemoglobin A1C (A1C) as a diagnosis tool and follow-up in type 2 Diabetes patients and their cut point levels for diagnosis and therapeutic targets according medical speciality.